2022
DOI: 10.1155/2022/1051046
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Involved in the High Incidence of Bladder Cancer in an Industrialized Area in North‐Eastern Spain

Abstract: Background. Bladder cancer (BC) is the most common of those affecting the urinary tract, and a significant proportion of the cases are attributable to tobacco use as well as occupational and environmental factors. Objective. The aim of this study is to estimate the current incidence of BC in an industrialized area in northeastern Spain and to analyze its time trends over three decades from an ecological perspective. Methods. Patients diagnosed with histologically confirmed primary BC, during 2018-2019, in an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The textile industry constituted the economic base of the Vallès Occidental region from the mid-19th century to the 1970s. This fact justified the performance of BC incidence and population-based case–control studies whose objectives were to assess occupational risk factors for BC in this area [ 5 , 13 , 17 ]. These studies demonstrated that tobacco consumption was strongly associated with BC [ 13 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The textile industry constituted the economic base of the Vallès Occidental region from the mid-19th century to the 1970s. This fact justified the performance of BC incidence and population-based case–control studies whose objectives were to assess occupational risk factors for BC in this area [ 5 , 13 , 17 ]. These studies demonstrated that tobacco consumption was strongly associated with BC [ 13 ].…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of BC in Vallès Occidental remains one of the highest in men and one of the lowest in women, at a European and global level, despite the decline in tobacco consumption and industrial activity over the years [ 6 ]. Compared to data published during the period 1992–1994, both the crude annual incidence and age-adjusted incidence have increased in both sexes, although the increase in men is notably higher [ 5 , 13 ]. The high incidence of BC in men, some 25 years later, could be related to a high prevalence in this area of well-known risk factors such as smoking, residence in industrialized areas, and occupational exposure to certain carcinogenic products [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently carried out a study on the high incidence of BC in an industrialized Mediterranean area, which has led us to consider the comparability of the incidence of BC between the different registries. 32 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, not only BC has a high rate of recurrence, but also generally presents as multicentric, and in some cases with a strong potential for infiltration, even if the invasion of the submucosa is not observed in the anatomopathological sample. We have recently carried out a study on the high incidence of BC in an industrialized Mediterranean area, which has led us to consider the comparability of the incidence of BC between the different registries 32 …”
Section: Discussionmentioning
confidence: 99%